If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -9x = 13 + -6x Solving 4 + -9x = 13 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 4 + -9x + 6x = 13 + -6x + 6x Combine like terms: -9x + 6x = -3x 4 + -3x = 13 + -6x + 6x Combine like terms: -6x + 6x = 0 4 + -3x = 13 + 0 4 + -3x = 13 Add '-4' to each side of the equation. 4 + -4 + -3x = 13 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 13 + -4 -3x = 13 + -4 Combine like terms: 13 + -4 = 9 -3x = 9 Divide each side by '-3'. x = -3 Simplifying x = -3
| 8*x*4= | | 2.9x-10.7=-2 | | 2y+8x+12=0 | | 8x-5=4x-3 | | -1=-96+b | | 40+2x+10=180 | | -5(3t-4)+4t=6t-8 | | -5y=.4 | | 4(x-5)-5=-6+7.4-4x | | -82=c-5 | | -3+2x=5x-36 | | 3r-8=-24 | | F(X)=100(1.04)200 | | 3(z+4)+6= | | 82=u-63 | | 12+2x+4y= | | 200=100(1.04)x | | h-9.2=28 | | 34x+4=106 | | F(200)=100(1.04)x | | -134-10x=58+2x | | -87=9+x | | 6x^2+12x^2-7x= | | F(200)=100(1.04)200 | | X+7=1+7x | | -54=-42+n | | x+13y+8y= | | x+3-2x=75 | | 9*n=2.5 | | 2a+4a=1 | | Z+4(z+3)=15 | | 9=8y |